Challenges and Advances in the Taxonomy of Deep-Sea Peracarida: From Traditional to Modern Methods - Frutos, Inmaculada; Kaiser, Stefanie; Pułaski, Łukasz; Studzian, Maciej; Błażewicz, Magdalena (Frontiers in Marine Science, 2022)
As one of the oldest branches of biology, taxonomy deals with the identification, classification and naming of living organisms using a variety of tools to explore traits at the morphological and molecular level. In the deep sea, particular challenges are posed to the taxonomic differentiation of species, which are mainly related to our general lack of knowledge about the deep sea, i.e. most of the deep-sea species brought to light are new. The resulting scarce knowledge of intraspecific variation makes it difficult to recognize species boundaries and thus to assess the actual diversity and distribution of species. In this review article, we highlight some of these challenges in deep-sea taxonomy using the example of peracarid crustaceans. Specifically, we offer a detailed overview of traditional as well as modern methods that are used in the taxonomic analysis of deep-sea Peracarida. Furthermore, methods are presented that have not yet been used in peracarid taxonomy, but have potential for the analysis of internal and external structures in the future. The focus of this compilation is on morphological methods for the identification, delimitation and description of species, but methods that aid molecular analyses are also discussed, as they are an indispensable part of an integrative taxonomic approach. Even if methods for the taxonomic analysis of peracarids are highlighted here, these could also be of interest for other deep-sea taxa and thus support research into deep-sea diversity in general.